CDP7657, an anti-CD40L antibody lacking an Fc domain, inhibits CD40L-dependent immune responses without thrombotic complications: an in vivo study. Issue 1 (December 2015) - Shock, Anthony; Burkly, Linda; Wakefield, Ian; Peters, Christopher; Garber, Ellen; Ferrant, Janine; Taylor, Frederick; Su, Lihe; Hsu, Yen-Ming; Hutto, David; Amirkhosravi, Ali; Meyer, Todd; et al.
Abstract Introduction CD40 ligand (CD40L) blockade has demonstrated efficacy in experimental autoimmune models. However, clinical trials of hu5c8, an anti-human CD40L IgG1 antibody, in systemic lupus erythematosus (SLE) were halted due to an increased incidence of thrombotic events. This study evaluated CDP7657, a high affinity PEGylated monovalent Fab' anti-CD40L antibody fragment, to assess whether an Fc-deficient molecule retains efficacy while avoiding the increased risk of thrombotic events observed with hu5c8. Methods The potency and cross-reactivity of CDP7657 was assessed inin vitro assays employing human and non-human primate leukocytes, and the capacity of different antibody formats to activate plateletsin vitro was assessed using aggregometry and dense granule release assays. Given the important role CD40L plays in regulating humoral immunity, in vivo efficacy was assessed by investigating the capacity of Cynomolgus monkeys to generate immune responses to the tetanus toxoid antigen while the potential to induce thrombotic eventsin vivo was evaluated after repeat dosing of antibodies to Rhesus monkeys. A PEGylated anti-mouse CD40L was generated to assess efficacy in the New Zealand Black/White (NZB/W) mouse model of SLE. Results CDP7657 dose-dependently inhibited antigen-specific immune responses to tetanus toxoid in Cynomolgus monkeys, and in contrast to hu5c8, there was no evidence of pulmonary thrombovasculopathy in Rhesus monkeys. Aglycosyl hu5c8, which lacks Fc receptor binding function, also failed to induce thrombotic events in Rhesus monkeys.In vitro experiments confirmed that antibody constructs lacking an Fc, including CDP7657, did not induce human or monkey platelet activation. A PEGylated monovalent Fab' anti-mouse CD40L antibody also inhibited disease activity in the NZB/W mouse model of SLE after administration using a therapeutic dosing regimen where mice received antibodies only after they had displayed severe proteinuria. Conclusions These findings demonstrate for the first time that anti-CD40L antibodies lacking a functional Fc region do not induce thrombotic events in Rhesus monkeys and fail to activate plateletsin vitro but, nevertheless retain pharmacological activity and support the investigation of CDP7657 as a potential therapy for systemic lupus erythematosus and other autoimmune diseases.